1992
DOI: 10.2527/1992.7061775x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting dystocia and early calf mortality in Angus cows and heifers1

Abstract: Calving performance records (965,417) from purebred American Angus herds throughout the United States were used to study dystocia and early calf mortality during the period from 1972 to 1985. A sample of 53 (n = 83,467) herds was used to establish reasonable limits on the expected frequency of dystocia and mortality within and among herds that have good reproductive management programs and to verify the frequencies of scores in all other herds (n = 4,130) reporting calving performance information. The data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
47
1
5

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 0 publications
13
47
1
5
Order By: Relevance
“…Chromosomes 2, 16 and 12 Birth weight is known to be non-linearly associated with dystocia and perinatal mortality, with lighter and heavier than average calves tending to have an increased risk of mortality and dystocia (Berger et al, 1992). Putative QTL regions affecting birth weight are well documented on chromosome 2; Grosz and MacNeil (2001) reported that ∼2.8 kg difference of birth weight could be accounted for by a QTL residing at the 114 cM region.…”
Section: Chromosome 18mentioning
confidence: 99%
See 1 more Smart Citation
“…Chromosomes 2, 16 and 12 Birth weight is known to be non-linearly associated with dystocia and perinatal mortality, with lighter and heavier than average calves tending to have an increased risk of mortality and dystocia (Berger et al, 1992). Putative QTL regions affecting birth weight are well documented on chromosome 2; Grosz and MacNeil (2001) reported that ∼2.8 kg difference of birth weight could be accounted for by a QTL residing at the 114 cM region.…”
Section: Chromosome 18mentioning
confidence: 99%
“…Dystocia and perinatal mortality are influenced by both environmental factors such as age at first calving and season of calving (McGuirk et al, 1999;Berry and Cromie, 2009) and also by genetic factors (Berger et al, 1992;Mee et al, 2011). Heritability estimates range from <0.01 to 0.17 for direct calving difficulty and <0.01 to 0.12 for the maternal components of calving difficulty (Steinbock et al, 2003;Hickey et al, 2007;Johanson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…CD PTA was reported to be critical for selecting beef sires to mate with either beef or dairy cows, which are expected to give rise to larger calves, whereas when selecting dairy sires, EBI was more important. Regarding parity, calving difficulty PTA became the key genetic trait when selecting both beef and dairy sires to mate to either beef or dairy heifers, likely due to the higher incidence of CD in heifers compared with cows (Berger et al, 1992;Nix et al, 1998), and to worse consequences of problems at calving in primiparous cows which lead to increase culling rates during first lactation (Lopez de Maturana et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that a breeding cow has a value of US$800, a calf weighs 227 kg at weaning and is valued at US$2.10 per kg when it is marketed at that time. Further, suppose the cost of pelvic measurement is US$3.00 per head, the cost of Cesarean Section is US$160 per head, and that the survival rate of a calf after a difficult birth is 0.9 or 90% [which is lower than that determined by Berger et al (1992)]. Expected returns of the scenarios are calculated using the revenues and costs defined above weighted by the predicted probabilities from the ordered logit model.…”
Section: Resultsmentioning
confidence: 99%
“…The principal cause of dystocia is the incompatibility of fetal size and maternal pelvic size, which has been the focus of various studies (Johnson et al 1988;Van Donkersgoed et al 1990;Berger et al 1992). We specify a basic biological system of two components of the birthing process, fetal BTW and maternal pelvic size.…”
Section: Conceptual Systemmentioning
confidence: 99%